THE MOST ABUNDANCE AND THE VERY RARE SPECIES IN THE DEEP SEA FISH COMMUNITY IN THE WESTERN SUMATERA, EASTERN INDIAN OCEAN - Badrudin Badrudin; Duto Nugroho; Ali Suman (Research Center for Fisheries, 2007)
Variation in species abundance provides one of the striking phenomena observed in ecological communities. This variation has led ecologists to pose central questions pertaining to the nature of communities. Most of the deep sea regions provide the most widely habitat, but until recently information on its community is very little.